UPGRADED TECHNOLOGY AND TECHNICAL SOLUTIONS FOR THE PREPARATION OF HEALTHY CONFECTIONERY VIROBITS (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The purpose of this study is to create a technology for the production of marmalade using a three-component vegetable and fruit paste, which includes pumpkin, apples and dogwood.The development of vegetable and fruit paste solves important tasks: ensuring the necessary structure of marmalade, achieving high organoleptic indicators without the use of artificial dyes and essences, enriching the chemical composition and giving the product functional properties. Due to the use of short-term low-temperature concentration and the optimal ratio of raw materials (pumpkin, apple, dogwood), the paste is characterized by a high content of functional components. The study of its composition showed the presence of dynamic viscosity ‒ 280 Pa∙s, non-starch polysaccharides ‒ 3.89±0.11 g, vitamin C ‒ 1.89±0.05 mg, β-carotene ‒ 21.13±0.60 mg. For an effective concentration process at a temperature of 55…65 °C, a viscosity interval of 5 to 35 Pa∙s has been determined.The improved marmalade production technology ensures higher quality of the finished product. The marmalade mass before gelatinization at a temperature of 80…82 °C has a viscosity that is 24% higher than the control sample. An improved vacuum evaporator with an increased heating surface has been proposed for the process of boiling the marmalade mass. Processing the marmalade mass allows reducing the specific heat consumption by 40% compared to the traditional evaporator (MZS-320). The finished marmalade has a rich ruby color, a lingering consistency, an increased content of pectin substances and vitamin C ‒ almost twice as much as in the control sample. The product is also enriched with vitamins A, C, E, β-carotene and contains a greater amount of macro- and microelements.According to the content of pectin substances, vitamin A, β-carotene and potassium, marmalade can be classified as a functional product, since the daily requirement for these substances exceeds 10%. The proposed technology can be successfully implemented at confectionery enterprises.
Keywords: confectionery; marmalade; vacuum evaporator; functional ingredients; quality improvement